Effect of neuromuscular blockade on the bispectral index in critically ill patients - Eva Sanavia; Mirian García; Jimena del Castillo; Rafael González; Jesús López-Herce; Santiago Mencía (Elsevier, 2020)
Introduction: It has been suggested that neuromuscular blockade (NMB) affects the capacity of bispectral index (BIS) monitoring to measure consciousness in sedated children. Our aim was to analyse the impact of NMB on BIS values in critically ill children. Methods: We conducted a prospective observational study of children monitored with a BIS system that received a continuous infusion of vecuronium. We analysed data on clinical, diagnostic and haemodynamic variables, sedatives, analgesics, muscle relaxants, and BIS parameters. We compared BIS parameters before the use of a muscle relaxant, during its administration, before its discontinuation and for the 24 h following the end of the infusion. Results: The analysis included 35 patients (median age, 30 months). The most common diagnosis was heart disease (85%). The most frequent indication for initiation of NMB was low cardiac output (45%), followed by adaptation to mechanical ventilation (20%). Neuromuscular blockade did not produce a significant change in BIS values. We found a decrease was observed in electromyography (EMG) values at 6 h (34.9 ± 9.4 vs 31.2 ± 7; P = .008) and 12 h after initiation of NMB (34.9 ± 9.4 vs 28.6 ± 4.8; P =.006). We observed a small significant increase in BIS after discontinuation of NMB (from 42.7 ± 11 to 48.4 ± 14.5, P = .001), and 6 and 12 h later (51.3 ± 16.6; P = .015). There were no differences in the doses of sedatives or analgesics except for fentanyl, of which the dose was lowered after discontinuation of vecuronium. Conclusion: Continuous NMB produces small changes on BIS values that are not clinically significant and therefore does not interfere with BIS consciousness monitoring in critically ill children. Resumen: Introducción: Estudios previos sugieren que el bloqueo neuromuscular (BNM) altera la monitorización del índice bispectral (BIS) en los niños sedados. El objetivo fue analizar la repercusión del uso y suspensión del BNM en la monitorización BIS en niños críticamente enfermos. Métodos: Estudio observacional prospectivo. Se incluyeron los niños que recibían perfusiones intravenosas de vecuronio con monitorización BIS. Se analizaron variables clínicas, diagnósticas, hemodinámicas, sedoanalgesia y relajantes musculares y parámetros del BIS. Se compararon los valores del BIS antes del uso de relajantes neuromusculares (RNM), durante su administración, antes de su retirada y durante las 24 h siguientes a su suspensión. Resultados: Treinta y cinco pacientes (edad mediana 30 meses). El diagnóstico más frecuente fue cardiopatía (85%). Las indicaciones más frecuentes para iniciar RNM fueron bajo gasto cardiaco (45%) y adaptación a ventilación mecánica (20%). El BNM no produjo cambios significativos en los valores del BIS. Se observó una disminución de los valores del electromiograma a las 6 h (34.9 ± 9.4 vs 31.2 ± 7; p = 0.008) y a las 12 h del inicio de la perfusión de vecuronio (34.9 ± 9.4 vs 28.6 ± 4.8; p = 0.006). Tras retirar el vecuronio hubo un ligero aumento significativo del BIS (de 42.7 ± 11 a 48.4 ± 14.5, p = 0.001), así como en las siguientes 6 y 12 h (51.3 ± 16.6; p = 0.015). No hubo diferencias en las dosis de sedantes o analgésicos, excepto del fentanilo, que fue disminuido tras retirar el vecuronio. Conclusión: El BNM continuo produce pequeños cambios en los valores del BIS sin relevanciaclínica, y no altera la monitorización del nivel de conciencia del BIS en los niños críticamenteenfermos.